Implementation von Förderkonzepten zum Aufarbeiten von Verstehensgrundlagen: Strategien und Bedingungen aus Mathe sicher können (mathematica didactica, 2023)
Intervention programs should focus on gaps in students’ understanding of basic concepts (such as place value understanding or the meaning of operations). For Grade 5-7, the intervention program Mastering Math was developed and its effectiveness was shown for several modules of the intervention in three controlled trials. This article documents how such kind of intervention programs can be implemented widely in classroom practices; by material, personnel, and systemic strategies on different levels. The implementation research reveals insights into conditions of success for professional development, qualification of PD facilitators and their systemic embedding.